A study of the value of trabecular bone score in fracture risk assessment of postmenopausal women - Alireza Mirzaei; Seyed Adel Jahed; Marzieh Nojomi; Alireza Rajaei; Mozhdeh Zabihiyeganeh (Elsevier, 2018)
Objective: Trabecular Bone Score (TBS) is an index of bone microarchitecture that provides additional skeletal information to areal Bone Mineral Density (aBMD). Recently TBS data has been used to optimize the Fracture Risk Assessment Tool (FRAX) predictive value. The aim of this study was to evaluate the clinical value of TBS on FRAX algorithm. Materials and Methods: Among total of 358 postmenopausal Iranian women (mean age 61.3 ± 9.5 years) tested for aBMD and TBS, 184 osteopenic women were identified. Thoracolumbar spine X-ray done in all participants revealed twenty-one vertebral fractures. For the osteopenic group, FRAX and TBS adjusted FRAX (FRAX-TBS) were calculated and compared. Results: Mean TBS of the patients was 1.31 (±0.11). A significant correlation was found between TBS and spine aBMD (r = 0.50, p < 0.001) and TBS and femoral neck aBMD (r = 0.37, p < 0.0001). A strong positive correlation was observed between aBMD adjusted FRAX and FRAX-TBS in predicting the risk of major osteoporotic fracture (r = 0.90, p < 0.0001), and hip fracture (r = 0.97, p < 0.0001). According to the area under the receiver operating characteristics curve, the predictive value of the three different models using aBMD, TBS, and combination of aBMD and TBS were similar (0.765, 0.776, and 0.781, respectively; p = 0.19). The proportion of the women needed treatment remained unchanged using FRAX or FRAX-TBS. Conclusion: This study showed no clinical benefit for TBS in postmenopausal women. Adding TBS data to aBMD or FRAX neither improved aBMD predictive value for vertebral fracture nor changed the decision on treatment based on FRAX.